Motivational differences between whole blood and plasma donors already exist before their first donation experience. Issue 8 (24th December 2012) - Veldhuizen, Ingrid; van, Anne
<x xml:space="preserve">Abstract</x> Background The demand for plasma products has increased rapidly. It is therefore important to understand donating behavior by plasma donors. This study investigates whether motivational differences between whole blood and plasma donors already exist at the beginning of a donor career. Study Design and Methods New donors (n = 4861) were invited to fill out a questionnaire before their first donation (response, 61%). The questionnaire assessed variables from the Theory of Planned Behavior (intention, self‐efficacy, attitude, and norms), conscientiousness, and donation anxiety. Three years later it was determined who became whole blood or plasma donor. Multivariable linear regression analyses for intention were fitted separately for whole blood and plasma donors. A logistic regression analysis was executed to estimate the effect of intention at the beginning of a donor career on becoming a plasma donor. Results Plasma donors had a higher intention, self‐efficacy, attitude, and conscientiousness and a lower anxiety than whole blood donors. In plasma and whole blood donors, both self‐efficacy and cognitive attitude were positively related to intention but with different strength (plasma, β = 0.47 and β = 0.30; whole blood, β = 0.57 and β = 0.17). Having a high level of intention increased the odds of becoming a plasma donor (odds ratio, 1.33; 95% confidence interval, 1.12‐1.59). Conclusion Motivational differences already exist between future whole blood and plasma donors before their first donation. Although a feeling of self‐efficacy is necessary for all new donors, more favorable cognitions are important for future plasma donors. Recruitment strategies for plasma donors should focus on attracting the more self‐confident donors by highlighting the usefulness of plasma donation.